Evaluation of biocomposite putty with strontium and zinc co-doped 45S5 bioactive glass and sodium hyaluronate - Ozel, Cem; Cevlik, Cem Batuhan; Ozarslan, Ali Can; Emir, Ceren; Elalmis, Yeliz Basaran; Yucel, Sevil (ELSEVIER, 2023)
The application of powder or granule formed bioactive glasses in the defect area with the help of a liquid carrier to fill the defects is a subject of interest and is still open to development. In this study, it was aimed to prepare biocomposites of bioactive glasses incorporating different co-dopants with a carrier biopolymer and to create a fluidic material (Sr and Zn co-doped 45S5 bioactive glassessodium hyaluronate). All biocomposite samples were pseudoplastic fluid type, which may be suitable for defect filling and had excellent bioactivity behaviors confirmed by FTIR, SEM-EDS and XRD. Biocomposites with Sr and Zn co-doped bioactive glass had higher bioactivity considering the crystallinity of hydroxyapatite formations compared to biocomposite with undoped bioactive glasses. Biocomposites with high bioactive glass content had hydroxyapatite formations with higher crystallinity compared to biocomposites with low bioactive glass. Furthermore, all biocomposite samples showed non-cytotoxic effect on the L929 cells up to a certain concentration. However, biocomposites with undoped bioactive glass showed cytotoxic effects at lower concentrations compared to biocomposites with co-doped bioactive glass. Thus, biocomposite putties utilizing Sr and Zn co-doped bioactive glasses may be advantageous for orthopedic applications due to their specified rheological, bioactivity, and biocompatibility properties.
Keywords: Bioactive glass; Bioactivity; Biocomposite; Putty; Co -doped; Strontium and zinc; IN-VITRO BIOACTIVITY; GEL-DERIVED GLASSES; RHEOLOGICAL PROPERTIES; ENHANCED BIOACTIVITY; MECHANICAL-BEHAVIOR; BONE REGENERATION; BIOCOMPATIBILITY; SUBSTITUTION; ACID; FABRICATION; Biochemistry & Molecular Biology; Chemistry; Polymer Science